2012
DOI: 10.1002/ejic.201200163
|View full text |Cite
|
Sign up to set email alerts
|

2‐Halogeno‐1,3,2‐diselenaphospholanes with an Annelated Dicarba‐closo‐dodecaborane(12) Unit: Synthesis, Molecular Structure and Reactivity

Abstract: Exchange reactions of 2,2‐dimethyl‐4,5‐[1,2‐dicarba‐closo‐dodecaborano(12)]‐1,3‐diselena‐2‐silacyclopentane with phosphorus trihalides PX3 (X = Cl, Br, I) led to the corresponding phospholanes in high yield. The solid‐state structure of the iodide was determined by X‐ray crystallography. Treatment of the bromide with nBu3SnH afforded the parent phosphane. The reaction of the iodide with LiAlH4 in [D8]toluene proceeded very slowly and mainly gave the deuterated phosphane. All products were characterised in solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The best synthetic strategy starts from the silanes 6 (Scheme 4) (Wrackmeyer, 2012;Wrackmeyer, , 1929Wrackmeyer, -1948, although the di-lithium salts 3 (E = S, Se) can also be used (Wrackmeyer, 2007;Wrackmeyer, 2014, Dalton Trans.). However, the reactions of the silanes 6 with phosphorus halides afford the products in higher purity and much better yield.…”
Section: 3-dithia-and 13-diselena-2-phospholanes With An Annelatedmentioning
confidence: 99%
See 2 more Smart Citations
“…The best synthetic strategy starts from the silanes 6 (Scheme 4) (Wrackmeyer, 2012;Wrackmeyer, , 1929Wrackmeyer, -1948, although the di-lithium salts 3 (E = S, Se) can also be used (Wrackmeyer, 2007;Wrackmeyer, 2014, Dalton Trans.). However, the reactions of the silanes 6 with phosphorus halides afford the products in higher purity and much better yield.…”
Section: 3-dithia-and 13-diselena-2-phospholanes With An Annelatedmentioning
confidence: 99%
“…The phosphorus halides 11 are more stable than their oxygen analogues 7, since the disproportionation products analogous to 8 play a minor role for X = Cl and even less so for X = Br, I. Therefore, the halides can be used to generate the parent compound 13 (R = H) as well as the fluoride 14 (X = F, for E = S) (Scheme 5), at least in reaction solutions in order to measure the most relevant NMR data (Wrackmeyer, 2012;Wrackmeyer, 2014, Dalton Trans.). Figure 3 shows the results of some NMR spectroscopic measurements for 13 (E = S) as an instructive example (Wrackmeyer, 2014, Dalton Trans.).…”
Section: 3-dithia-and 13-diselena-2-phospholanes With An Annelatedmentioning
confidence: 99%
See 1 more Smart Citation
“…91 The XE{1,2-Se 2 C 2 B 10 H 10 } (E = B or P, X = halide) clusters were synthesised and demonstrated to undergo alkyne insertion into the B-Se bonds of the borolane moiety. 92,93 Metallaboranes, metallaheteroboranes and exo-metallaheteroboranes A number of new transition metal centred boron molecular wheels have been observed, including [MrB 9 ] À (M = Rh or Ir, compounds VII and VIII) and [M 0 rB 10 ] À (M 0 = Nb or Ta), the first deca-coordinated 2D structures. 94 Photoelectron spectroscopy suggested that the former have stable neutral forms, MrB 9 .…”
Section: Annual Reports a Reviewmentioning
confidence: 99%
“…Our interest in such compounds with an annelated 1,2‐dicarba‐ closo ‐dodecaborane(12) unit prompted us to explore the behavior of 1,3,2‐diselenaphospholanes 1 7 and 2 6,7 towards Lewis acids such as BH 3 (as adduct with THF or SMe 2 ), Br 2 BH–SMe 2 , and [Cp*MCl 2 ] 2 (M = Rh, Ir). Phospholanes 1 and 2 were selected because 1 stays mainly as a monomer in solution and 2 does not show any tendency at all for dimerization, and both 1 and 2 possess analogous solution‐state structures as far as the five‐membered rings are concerned 7,8. Furthermore, selenium may compete with phosphorus for the Lewis acid, in particular if the basicity of phosphorus is reduced.…”
Section: Introductionmentioning
confidence: 99%